Pengaruh Rekrutment dan Seleksi Terhadap Kinerja Karyawan pada PT. Gokko Mirai Indonesia - Reynalda Suryono; Asep Jamaludin; Nandang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to evaluate how the recruitment and selection process of PT. Gokkomirai Indonesia has an impact on employee performance. This study was conducted quantitatively, with samples taken using the random sampling method and the Slovin formula. A total of 250 employees responded and 192 samples were taken. The results showed that recruitment variables affected employee performance partially and significantly, with significance values of 0.002 < 0 > 1.652 in t table. Selection variables also affect employee performance partially and significantly, with significance values of 0.000 < 0 > 1.652 in t table. In the simultaneous test (f), both variables affect employee performance simultaneously, with significance values of 0.000 < 0 > 1.652 in t table. In the simultaneous test (f), recruitment and selection variables affect employee performance together, with a significance value of 0.000 < 0 > f-Table 2.65. Selection (X1) and recruitment (X2) variables contributed 64.3% to employee performance (Y). Hiring and selecting employees has an impact on the performance of PT Gokko Mirai Indonesia.